Increased aortic wall thickness on CT as a sign of prosthetic valve endocarditis. (December 2016) - Fagman, Erika; Bech-Hanssen, Odd; Flinck, Agneta; Lamm, Carl; Svensson, Gunnar
Background: Increased wall thickness in the aortic root has been suggested as an early sign of prosthetic valve endocarditis (PVE). However, there are no previous studies on the aortic wall thickness after aortic valve replacement (AVR) or in patients with PVE. Purpose: To identify a clinically useful cutoff value for aortic wall thickness to detect PVE. Material and Methods: Chest computed tomography (CT) studies (n = 303) on patients with a prosthetic aortic valve were retrospectively analyzed. CT studies on patients without PVE (n = 260) were compared with CT studies on patients with definite PVE (n = 43). A receiver operator characteristic (ROC) analysis was performed. Results: In non-PVE patients, the wall thickness during the first 3 months postoperatively (n = 70, 4.5 ± 1.7 mm) was increased compared to beyond 3 months postoperatively (n = 190, 3.2 ± 1.0 mm, P  < 0.001). Beyond 3 months postoperatively, the wall thickness 95th percentile was 5.0 mm without signs of further decrease with time. The wall thickness in PVE patients was 6.8 ± 3.0 mm (n = 43). Beyond 3 months postoperatively, ROC analysis yielded an area under the curve of 0.89 (95% CI, 0.81–0.96). With a cutoff value of 5 mm the sensitivity was 67%, specificity 95%, positive likelihood ratio 14.1, and negative likelihood ratio 0.35 of increased wall thickness in detecting PVE. Conclusion: In the early postoperative period after AVR, the aortic wall thickness is increased compared to the late postoperative period. After 3 months, the wall thickness has decreased and stabilized. Increased wall thickness (>5 mm) beyond 3 months postoperatively significantly increases the likelihood of PVE.